2021
DOI: 10.1038/s41524-021-00496-7
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics and materials design for embedded phase-change memory

Abstract: The Ge2Sb2Te5 alloy has served as the core material in phase-change memories with high switching speed and persistent storage capability at room temperature. However widely used, this composition is not suitable for embedded memories—for example, for automotive applications, which require very high working temperatures above 300 °C. Ge–Sb–Te alloys with higher Ge content, most prominently Ge2Sb1Te2 (‘212’), have been studied as suitable alternatives, but their atomic structures and structure–property relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 80 publications
3
42
0
Order By: Relevance
“…As an example of this methodology, we have computed the decomposition map of the three alloys, GST312, GST412 and GST512, on the Ge-GST124 pseudobinary line, whose amorphous phase was investigated by DFT simulations in Ref. [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example of this methodology, we have computed the decomposition map of the three alloys, GST312, GST412 and GST512, on the Ge-GST124 pseudobinary line, whose amorphous phase was investigated by DFT simulations in Ref. [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The phase separation itself is believed to be the origin of the raise of because of the mass transport on a long length scale involved in phase segregation [ 22 ]. However, previous analysis of DFT models of the amorphous phase as a function of composition revealed that moving away from the GeTe-Sb Te tie-line by increasing either the Ge or Sb content along the Ge-GST124 [ 27 ], Sb-GeTe [ 56 ] and Ge-Sb Te lines [ 42 ], leads to an amorphous network which is more and more dissimilar from the cubic crystal. In the rocksalt phase, all atoms are in an octahedral bonding geometry with no homopolar bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shorter the interatomic distance, the higher the bond population. Following our previous work, [106][107][108] we multiply the B AB by the RDF and obtain the "bond-weighted distribution function" BWDF ¼ P B>A ½δðr À jr AB jÞ Â B AB for the six amorphous alloys. The crossover from positive to negative values in the BWDFs determines a threshold for covalent interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The unique property of GeTe-Sb 2 Te 3 also makes it an excellent candidate for various applications in computer science, especially in the field of non-volatile computer memory [4,5]. Important progress has been achieved in the past 20 years to develop new phase change materials and understand their phase change mechanisms [6][7][8][9][10][11][12][13][14][15]. It has been known that local interactions between atoms play an important role in phase changes [4,16].…”
Section: Introductionmentioning
confidence: 99%